Cholesterol Crystals Induce Inflammatory Cytokines Expression in nARPE-19 Cells by Activating the NF-κB Pathway - Hu, Yijun (Discov Med, 2014)
PURPOSE: To investigate the expression of inflammatory cytokines in ARPE-19 cells after stimulation with cholesterol crystals. METHODS: APRE-19 cells were cultured, primed with IL-1α, and treated with cholesterol crystals under different concentrations. Inflammatory cytokines (mature-IL-1β, IL-6, and IL-8) in supernatant and inflammatory cytokines (pro-IL-1β, IL-18) in cell lysate were detected by western blot. The NF-κB pathway inhibitor BAY 11-7082 was used to determine the pathway of cytokine expression. RESULTS: Cholesterol crystals did not induce the nucleotide-binding domain leucine-rich repeat containing family, pyrin domain containing 3 (NLRP3) inflammasome, but did increase pro-IL-1β expression in ARPE-19 cells. Cholesterol crystals increased pro-IL-1β expression by activating the NF-κB pathway. Cholesterol crystal activation of the NF-κB pathway also leads to increased IL-6 and IL-8 expression. CONCLUSION: Cholesterol crystals can induce inflammatory cytokine expression in ARPE-19 cells by activating the NF-κB pathway.